2020
DOI: 10.3892/mmr.2020.11589
|View full text |Cite
|
Sign up to set email alerts
|

Salvianolic acid B alleviates myocardial ischemic injury by promoting mitophagy and inhibiting activation of the NLRP3 inflammasome

Abstract: ischemic heart disease is a major cause of mortality and disability worldwide. Salvianolic acid B (Sal B) is one of the main water-soluble components of Salvia miltiorrhiza Bge. numerous studies have demonstrated that Sal B could exert significant anti-inflammatory and cardiovascular protective effects; however, the underlying mechanisms remain unclear. To elucidate the association between myocardial ischemia and inflammation, and to develop effective protective drugs, a rat model of myocardial ischemia was in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“…Redix Salvia miltiorrhizae is a traditional medicinal plant, which is widely used in Asian countries due to its pharmacological effects. Studies have shown that one of its active ingredients, Redix Salvia miltiorrhiza , has obvious anti-inflammatory and cardiovascular protective effects ( Hu et al, 2020 ). Another active ingredient, Protocatechualdehyde, is a major component of salvia miltiorrhiza that reduces cardiovascular ischemic injury by inhibiting the ER stress-related PERK, IRE1α, and ATF6α signaling pathways ( Wan et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Redix Salvia miltiorrhizae is a traditional medicinal plant, which is widely used in Asian countries due to its pharmacological effects. Studies have shown that one of its active ingredients, Redix Salvia miltiorrhiza , has obvious anti-inflammatory and cardiovascular protective effects ( Hu et al, 2020 ). Another active ingredient, Protocatechualdehyde, is a major component of salvia miltiorrhiza that reduces cardiovascular ischemic injury by inhibiting the ER stress-related PERK, IRE1α, and ATF6α signaling pathways ( Wan et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In lipopolysaccharide + adenosine triphosphate-administrated H9C2 cells, salvianolic acid B markedly prevents ROS production, NLRP3 inflammasome-mediated inflammatory response and cell apoptosis, and enhances mitochondrial membrane potential. Further evidence has confirmed that salvianolic acid B promotes SIRT1-mediated mitophagy to restore mitochondrial function, thereby preventing myocardial ischemic injury ( Hu et al, 2020 ). Accumulating evidence has demonstrated that NLRP3 inflammasome-regulated inflammatory responses are responsible for the development of atherosclerosis.…”
Section: Phytochemical-mediated Mitophagy In Metabolic Disordersmentioning
confidence: 97%
“…Salvianolic acid B, as one of the main water-soluble components of Salvia miltiorrhiza Bunge, has significant anti-inflammatory and cardiovascular protective effects. Hu et al (2020 ) established a myocardial ischemia model and H9C2 cell inflammation model in rats and treated them with different concentrations of salvianolic acid B. Results showed that salvianolic acid B could significantly decrease acute myocardial ischemic injury in rats, significantly inhibit the production of ROS in H9C2 cells, increase the mitochondrial membrane potential, inhibit activation of the NLRP3 inflammasome, and inhibit apoptosis.…”
Section: Potential Action Mechanisms Of Tcm For Cmvdmentioning
confidence: 99%